2021
DOI: 10.1144/jgs2020-217
|View full text |Cite
|
Sign up to set email alerts
|

Quo vadis Zeus : is there a Zas shear zone on Naxos Island, Aegean Sea, Greece? A review of metamorphic history and new kinematic data

Abstract: Detecting zones of considerable early-orogenic displacement in rather monotonous rock sequences which have undergone a late and pervasive tectonometamorphic overprint is challenging. It has been proposed that the alleged Zas shear zone in the passive-margin sequence of the Cycladic Blueschist Unit (CBU) on Naxos Island, Greece, separates amphibolite-facies, non-high-P rocks (Koronos Unit) below from Eocene high-P rocks (Zas Unit) above the shear zone. We review existing pressure-temperature (P-T) data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…However, the data by Kumerics et al (2005) from Ikaria Island also show low kinematic vorticity but the shear sense during extensional shearing at the Ikaria segment of the North Cyclades detachment system is predominantly top-N (see also Beaudoin et al, 2015). A similar, but less well constrained case can be made for the Naxos-Paros detachment system for which Peillod, Tehler, et al (2021) showed a distinct degree of coaxial deformation during extensional shearing associated with a dominant top-N sense of shear. Collectively, these data support distinct vertical flattening during large-scale ductile extension but pronounced vertical flattening does not appear a limiting factor causing the extensional hinge zone to form.…”
Section: Extensional Hinge Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the data by Kumerics et al (2005) from Ikaria Island also show low kinematic vorticity but the shear sense during extensional shearing at the Ikaria segment of the North Cyclades detachment system is predominantly top-N (see also Beaudoin et al, 2015). A similar, but less well constrained case can be made for the Naxos-Paros detachment system for which Peillod, Tehler, et al (2021) showed a distinct degree of coaxial deformation during extensional shearing associated with a dominant top-N sense of shear. Collectively, these data support distinct vertical flattening during large-scale ductile extension but pronounced vertical flattening does not appear a limiting factor causing the extensional hinge zone to form.…”
Section: Extensional Hinge Modelmentioning
confidence: 83%
“…Mizera and Behrmann (2016) across the Cyclades with 47 data points and the tensor average of all data plotting in the oblate field. Peillod, Tehler, et al (2021) also described oblate-strain geometry from the CBU on Naxos and suggested that extensional shearing had a distinct pure-shear component. Xypolias (2010) reported near-plane-strain geometry from the lowermost CBU (and W m of 0.8-0.9) and prolate-strain geometry from the top of the CBU section (W m of 0.6-0.9) on Evia Island.…”
Section: Finite Strain and Kinematic Vorticitymentioning
confidence: 97%
“…Schematic P–T–t diagram, redrawn after Peillod, Majka, et al (2021) and Peillod, Tehler, et al (2021). P–T–t paths for the top of the middle‐CBU nappe near Kalados Bay (in blue), the central section of the middle‐CBU nappe (green path).…”
Section: Discussionmentioning
confidence: 99%
“…Metamorphic zones range from the migmatitic core (approximately 700°C) to greenschist grade in the south of the island. Yellow stars: samples used by Peillod et al (2017), Peillod, Majka, et al (2021),and Peillod, Tehler, et al (2021) for P – T path analyses. Green stars: aliquots of the Peillod et al (2017) samples analysed in the present work…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation